Effect of CYP2C9-VKORC1 interaction on warfarin stable dosage and its predictive algorithm - Li, Xi; Liu, Rong; Yan, Han; Tang, Jie; Yin, Ji-Ye; Mao, Xiao-Yuan; Yang, Fang; Luo, Zhi-Yin; Tan, Sheng-Lan; He, Hui; Chen, Xiao-Ping; Liu, Zhao-Qian; et al. (Journal of clinical pharmacology, 2015)
This study aimed to identify the effect of CYP2C9–VKORC1 interaction on warfarin dosage requirement and its predictive algorithm by investigating four populations. Generalized linear model was used to evaluate the relationship between the interaction and warfarin stable dosage (WSD), whereas multiple linear regression analysis was applied to construct the WSD predictive algorithm. To evaluate the effect of CYP2C9–VKORC1 interaction on the predictive algorithms, we compared the algorithms with and without the interaction. The interaction was significantly associated with WSD in the Chinese and White cohorts (P values < 0.05). In the algorithms that considered the interaction, the predictive success rates improved by only 0.12% in the Chinese patients and by a maximum of 0.02% in the White patients under four different CYP2C9 classifications. Thus, VKORC1–CYP2C9 interaction can affect WSD. However, the discrepancy between the predictive results obtained using the predictive algorithm with and without CYP2C9–VKORC1 interaction was negligible and can therefore be disregarded.